Isolation and Characterization of Xanthine Oxidase from Goats Milk - Rohma, Maretha Nur; Herdyastuti, Nuniek (Jurnal Pijar Mipa, 2025)
Xanthine oxidase (XO) plays a role in the formation of uric acid and can be obtained from various sources, including goat's milk. This study aims to provide xanthine oxidase enzymes with known purity, characteristics (pH, temperature, and molecular weight), and to determine the effect of the inhibitor allopurinol on xanthine oxidase enzyme activity. Isolation is carried out using NaCl and partial purification through acetone precipitation. Enzyme activity is determined by the amount of uric acid formed in each acetone fraction, while protein levels are analyzed by the Bradford method. Results showed that the 60-90% acetone fraction provided the highest specific activity, with a purity of 29.190%. The enzyme showed optimum activity at pH 7.5 and temperature 33 °C, and a molecular weight of about 65 kDa. The inhibition test showed that the higher the concentration of allopurinol used, the greater the percentage of inhibition produced. The concentration of allopurinol 2 ppm provides the highest inhibition percentage of 90.376%. The xanthine oxidase enzyme produced from the research is expected to provide xanthine oxidase enzyme from goat milk that can be utilized further, both for research on the mechanism of inhibition of enzyme activity, as well as applications in other fields.